Drying Characteristics of Indian Cheese at Low Superheated Steam Drying - Shrivastav, Shivamurti; Kumbhar, B K (Journal of Agricultural Engineering, 2009)
Indian cheese is an important dairy product and is used to prepare different culinary dishes. It is highly perishable in nature at ambient conditions and its shelf life is very low. The product develops a sour smell, bitter taste and being sparsely covered with moulds when expressed to high temperature. This study was undertaken to investigate the drying characteristics of Indian cheese, at low pressure superheated steam drying (LPSSD). The effect of steam temperature (62, 72 and 82degree C) and pressure (10, 14 and 18 kpa) on drying rates was determined. Page’s model was selected as a better predictive model as compared to exponential and logarithmic models.